Loop-mediated isothermal amplification combined with lateral flow biosensor for rapid and sensitive detection of monkeypox virus - Xiaolan Huang; Fei Xiao; Nan Jia; Chunrong Sun; Jin Fu; Zheng Xu; Xiaodai Cui; Hui Huang; Dong Qu; Juan Zhou; Yi Wang (Frontiers Media S.A., 2023)
The ongoing outbreak of the monkeypox, caused by monkeypox virus (MPXV), has been a public health emergency of international concern, indicating an urgent need for rapid and sensitive MPXV detection. Here, we designed a diagnostic test based on loop-mediated isothermal amplification (LAMP) and nanoparticle-based lateral flow biosensor(LFB)for diagnosis of MPXV infection, termed MPX-LAMP-LFB. A set of six LAMP primers was designed based the ATI gene of MPXV, and LAMP amplification of MPXV templates was performed at 63°C for only 40 min. The results were rapidly and visually decided using the LFB test within 2 min. The MPX-LAMP-LFB assay can specifically detect MPXV strains without cross-reaction with non-MPXV pathogens. The sensitivity of the MPX-LAMP-LFB assay is as low as 5 copies/μl of plasmid template and 12.5 copies/μl of pseudovirus in human blood samples. The whole process of the MPX-LAMP-LFB assay could be completed ~1 h, including rapid template preparation (15 min), LAMP reaction (40 min)and result reporting (<2 min). Collectively, MPX-LAMP-LFB assay developed here is a useful tool for rapid and reliable diagnosis of MPXV infection.